Fe-Ni-Co-Al-Cr superelastic alloy with ultrahigh strength and preparation method of Fe-Ni-Co-Al-Cr superelastic alloy

By adding Cr elements to the Fe-Ni-Co-Al superelastic alloy and heat treatment, Fe0.64Ni0.36 phase was formed, and the problems of poor superelasticity and limited strength of Fe-based superelastic alloys were solved, and ultra-high strength and excellent superelastic properties were achieved, which were suitable for a variety of application fields.

CN119685712APending Publication Date: 2025-03-25GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410495205.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-24
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Fe-based superelastic alloys have poor superelasticity and limited strength at room temperature, which limits their application in bridge construction, aerospace and other fields.

Method used

By adding Cr elements to the Fe-Ni-Co-Al superelastic alloy, and adjusting the element ratio and reasonable heat treatment process, Fe0.64Ni0.36 phase is formed, which greatly enhances the plasticity of the matrix and obtains ultra-high strength and large resilient strain.

Benefits of technology

It achieves ultra-high strength and excellent super elastic properties, improves the compressive strength and resilient strain of the alloy, improves its processing performance and friction wear performance, and is suitable for a wide range of application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685712A_ABST
    Figure CN119685712A_ABST
Patent Text Reader

Abstract

The invention provides a Fe-Ni-Co-Al-Cr superelastic alloy and a preparation method thereof, the expression of the superelastic alloy is FeaNibCocAldCre, a, b, c, d and e respectively represent the atomic number percentage (at.%) of corresponding elements, a = 35-50, b = 20-35, c = 10-20, d = 5-18, and e = 0-3. The preparation method of the superelastic alloy comprises the steps of smelting, solid solution treatment and aging treatment. According to the superelastic alloy and the preparation method thereof, phase formation is regulated and controlled by adjusting the element ratio and the heat treatment process, so that excellent superelasticity and excellent friction and wear performance are obtained, the maximum deformation of the superelastic alloy is larger than or equal to 99%, the compressive strength exceeds 5100 MPa, and the recoverable strain is 12.5%. The method is simple in process, can be used for preparing superelastic alloys in various different shapes due to the excellent plasticity of the superelastic alloy, and is suitable for large-scale industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a Fe-Ni-Co-Al-Cr alloy with superelasticity and a preparation method thereof, belonging to the technical field of iron-based superelastic alloy materials. Background Art

[0002] Superelasticity (SE) is defined as the shape recovery of the deformation in the austenite phase after unloading, that is, the alloy is subjected to a complete loading-unloading cycle, and after unloading, the alloy can completely recover to the shape before deformation. General metal materials deform under the action of external forces. When the deformation is greater than its elastic stage, the material will undergo permanent plastic deformation and cannot recover its original shape. The recoverable deformation of general metal materials is often limited to about 0.2%, but for superelastic alloys, even if the deformation is much greater than the elastic stage, it can still recover after unloading. Superelastic alloys have broad application prospects in bridge construction, aerospace, seismic shock absorption, medical electronics, transportation energy, etc. Nowadays, Cu-based, Ni-Ti-based and Fe-based alloys are widely used in superelastic alloys. Among them, Fe-based superelastic alloys have attracted widespread attention due to their lower cost. However, Fe-based alloys have poor superelasticity and limited strength at room temperature, which limits their further application.

[0003] In 2010, Tanaka et al. reported that Fe-28Ni-17Co-11.5Al-2.5Ta-0.05B ​​(at%) alloy has excellent superelasticity, high strength, high hardness and processing performance. Its maximum recoverable strain at room temperature reaches 13.5%, and in 2015, the optimal alloy composition design ratio was given.

[0004] In 2016, YIChumlyakov et al. studied the tensile superelastic response of single crystals oriented along the

[001] direction at different temperatures after aging Fe-28Ni-17Co-11.5Al-2.5Nb at 973K for 0.5 hours, and found that aging treatment led to the formation of ordered γ' particles with a particle size of less than 3nm. A reversible strain of up to 15.3% was observed at 77K, which is the highest value ever reported for iron-based shape memory alloys.

[0005] The present invention adds Cr to the Fe-Ni-Co-Al superelastic alloy to improve its wear performance. 0.64 Ni 0.36 The formation of phases can greatly enhance the plasticity of the matrix, with a maximum deformation of ≥99%, providing conditions for stress-induced martensitic transformation. And through the compression process with a large deformation of ≥80%, a strong texture is obtained, thereby obtaining ultra-high strength and a large recoverable strain. Summary of the invention

[0006] The invention provides a Fe-Ni-Co-Al-Cr superelastic alloy and a preparation method thereof. The superelastic alloy has ultrahigh strength and excellent superelasticity and processing performance.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] A Fe-Ni-Co-Al-Cr superelastic alloy, the composition of the superelastic alloy is Fe a Ni b Co c Al d Cr e , wherein a, b, c, d, e represent the atomic percentage (at.%) of the corresponding element, a=35~50, b=20~35, c=10~20, d=5~18, e=0~3, and some inevitable impurities.

[0009] The molecular formula of the Fe-Ni-Co-Al-Cr superelastic alloy is preferably Fe (37~43) Ni (23~35) Co (10~20) Al (5~19) Cr (0~5) , more preferably Fe (40~43) Ni (30~35) Co (15~20) Al (9~12) Cr (0~3) , most preferably Fe 42 Ni 30 Co 16 Al 11 Cr1.

[0010] A method for preparing a Fe-Ni-Co-Al-Cr superelastic alloy comprises the following steps:

[0011] (1) Alloy smelting. Iron, nickel, cobalt, aluminum and chromium are weighed in proportion and arc-melted in a non-consumable vacuum arc furnace to obtain metal ingots for use;

[0012] (2) Heat treatment: The heat treatment includes solution treatment and aging treatment.

[0013] Preferably, the metallic iron, nickel, cobalt, aluminum and chromium are metallic single substances, and the purity of the metallic iron, nickel, cobalt, aluminum and chromium is preferably 99.9%.

[0014] Preferably, the vacuum degree during smelting is less than 3×10 -3 Pa, and the smelting process is carried out under argon protection.

[0015] Preferably, the metal ingot during smelting is turned over and smelted repeatedly for more than three times to ensure uniform alloy composition.

[0016] Preferably, the heat treatment process is: solution treatment + aging treatment.

[0017] The solution treatment temperature is preferably 1200° C., the time is preferably 1 to 3 hours, more preferably 2 hours. The aging temperature is preferably 600° C., the time is preferably 5 to 260 hours, more preferably 52 hours.

[0018] The present invention provides a Fe-Ni-Co-Al-Cr superelastic alloy and a preparation method thereof, which has the following advantages over the prior art:

[0019] (1) The alloy prepared by the present invention has a reasonable composition ratio of each element and a reasonable heat treatment process, so that the alloy parent phase has a single FCC structure, which promotes the formation of Fe 0.64 Ni 0.36 Phase, the formation phase can greatly enhance the plasticity of the matrix, which is conducive to the occurrence of stress-induced martensitic phase transformation. And through the compression process of ≥80% large deformation, a strong texture is obtained, thereby obtaining ultra-high strength and large recoverable strain. Compared with the existing Fe-based superelastic alloy, its ultra-high compressive strength and processability, as well as low cost make it have broad application prospects and are very attractive in business, especially for load-bearing columns.

[0020] (2) Cr greatly improves the friction and wear properties of the alloy, making it more suitable for application in various fields.

[0021] (3) The present invention provides the Fe-Ni-Co-Al-Cr superelastic alloy and a preparation method thereof. An ultra-high strength superelastic alloy can be obtained by smelting, solid solution + aging treatment. The preparation process is simple and low-cost and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Fe prepared in Example 1 of the present invention 42 Ni 24 Co 14 Al 18 Stress-strain curve of Cr2 under loading-unloading at room temperature;

[0023] Figure 2 Fe prepared in Example 2 of the present invention 41 Ni 26 Co 16 Al 16 Stress-strain curve of Cr2 under loading-unloading at room temperature;

[0024] Figure 3Fe prepared in Example 3 of the present invention 41 Ni 30 Co 16 Al 11 Stress-strain curve of Cr1 under loading-unloading at room temperature;

[0025] Figure 4 is Fe in Example 4 of the present invention 41 Ni 30 Co 16 Al 11 Stress-strain curves of Cr1 alloy after solution treatment at 1200℃ for 2h and then aging at 600℃ for 12h under loading-unloading at room temperature;

[0026] Figure 5 is Fe in Example 5 of the present invention 41 Ni 30 Co 16 Al 11 Stress-strain curves of Cr1 alloy after solution treatment at 1200℃ for 2h and then aging at 600℃ for 21h under loading-unloading at room temperature;

[0027] Figure 6 is Fe in Example 6 of the present invention 41 Ni 30 Co 16 Al 11 Stress-strain curves of Cr1 alloy after solution treatment at 1200℃ for 2h and then aging at 600℃ for 52h under loading-unloading at room temperature;

[0028] Figure 7 is Fe in Example 7 of the present invention 41 Ni 30 Co 16 Al 11 Stress-strain curves of Cr1 alloy after solution treatment at 1000℃ for 8h and then aging at 600℃ for 21h under loading-unloading at room temperature;

[0029] Figure 8 is Fe in Example 8 of the present invention 41 Ni 30 Co 16 Al 11 Stress-strain curves of Cr1 alloy after solution treatment at 1000℃ for 8h and then aging at 600℃ for 50h under loading-unloading at room temperature;

[0030] Fig. 9 Fe prepared in Example 3 of the present invention 41 Ni 30 Co 16 Al 11 Cr1 and Fe prepared in Comparative Example 1 41 Ni30 Co 16 Al 11 Cr2 and Fe prepared in Comparative Example 2 43 Ni 30 Co 16 Al 11 Graph showing the variation of friction coefficient of superelastic alloy over time;

[0031] Fig.10 Fe prepared in Example 3 of the present invention 41 Ni 30 Co 16 Al 11 Cr1 and Fe prepared in Comparative Example 1 41 Ni 30 Co 16 Al 11 Cr2 and Fe prepared in Comparative Example 2 43 Ni 30 Co 16 Al 11 Wear scar depth versus displacement curve for superelastic alloy; DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the present invention are clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1:

[0034] (1) According to the molecular formula Fe 42 Ni 24 Co 14 Al 18 Cr2 weighed 11.345g of 99.99% pure iron, 6.8125g of nickel, 3.9905g of cobalt, 2.3488g of aluminum and 0.5030g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0035] (2) Cut the ingot into the size of 4 mm × 4 mm × 8 mm.

[0036] Embodiment 2:

[0037] (1) According to the molecular formula Fe 41 Ni 26 Co16 Al 16 Cr2 Weigh 10.66g of 99.99% pure iron, 7.825g of nickel, 4.4997g of cobalt, 2.060g of aluminum and 0.4963g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reaches 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0038] (2) Cut the ingot into the size of 4 mm × 4 mm × 8 mm.

[0039] Embodiment 3:

[0040] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11 Cr1 weighed 10.8635g of 99.99% pure iron, 8.1543g of nickel, 4.3667g of cobalt, 4.3744g of aluminum and 0.2408g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0041] (2) Cut the ingot into the size of 4 mm × 4 mm × 8 mm.

[0042] Embodiment 4:

[0043] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11 Cr1 weighed 10.8635g of 99.99% pure iron, 8.1543g of nickel, 4.3667g of cobalt, 4.3744g of aluminum and 0.2408g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0044] (2) Cut the ingot into a size of 10 mm × 10 mm × 25 mm. Seal the sample in a vacuum quartz glass tube.

[0045] (3) The sealed sample was solution treated at 1200°C for 2 h and then water quenched.

[0046] (4) The alloy in (3) was aged at 600°C for 12 h and then water quenched.

[0047] Embodiment 5:

[0048] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11 Cr1 weighed 10.8635g of 99.99% pure iron, 8.1543g of nickel, 4.3667g of cobalt, 4.3744g of aluminum and 0.2408g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0049] (2) Cut the ingot into a size of 10 mm × 10 mm × 25 mm. Seal the sample in a vacuum quartz glass tube.

[0050] (3) The sealed sample was solution treated at 1200°C for 2 h and then water quenched.

[0051] (4) The alloy in (3) is then aged at 600°C for 21 h and then water quenched.

[0052] Embodiment 6:

[0053] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11 Cr1 weighed 10.8635g of 99.99% pure iron, 8.1543g of nickel, 4.3667g of cobalt, 4.3744g of aluminum and 0.2408g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0054] (2) Cut the ingot into a size of 10 mm × 10 mm × 25 mm. Seal the sample in a vacuum quartz glass tube.

[0055] (3) The sealed sample was solution treated at 1200°C for 2 h and then water quenched.

[0056] (4) The alloy in (3) is then aged at 600°C for 52 h and then water quenched.

[0057] Embodiment 7:

[0058] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11Cr1 weighed 10.8635g of 99.99% pure iron, 8.1543g of nickel, 4.3667g of cobalt, 4.3744g of aluminum and 0.2408g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0059] (2) Cut the ingot into a size of 10 mm × 10 mm × 25 mm. Seal the sample in a vacuum quartz glass tube.

[0060] (3) The sealed sample was solution treated at 1000°C for 8 h and then water quenched.

[0061] (4) The alloy in (3) is then aged at 600°C for 21 h and then water quenched.

[0062] Embodiment 8:

[0063] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11 Cr1 weighed 10.8635g of 99.99% pure iron, 8.1543g of nickel, 4.3667g of cobalt, 4.3744g of aluminum and 0.2408g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reached 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0064] (2) Cut the ingot into a size of 10 mm × 10 mm × 25 mm. Seal the sample in a vacuum quartz glass tube.

[0065] (3) The sealed sample was solution treated at 1000°C for 8 h and then water quenched.

[0066] (4) The alloy in (3) is then aged at 600°C for 50 h and then water quenched.

[0067] Comparative Example 1:

[0068] Preparation of Fe 41 Ni 30 Co 16 Al 11 Cr2 alloy:

[0069] (1) According to the molecular formula Fe 41 Ni 30 Co 16 Al 11Cr2 Weigh 10.6125g of 99.99% pure iron, 8.1601g of nickel, 4.3698g of cobalt, 1.3754g of aluminum and 0.4819g of chromium, and put them into a non-consumable vacuum melting furnace for melting. The furnace vacuum reaches 3.0×10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0070] (2) Cut the ingot into the size of 2 mm × 6 mm × 13 mm.

[0071] Comparative Example 2:

[0072] Preparation of Fe 43 Ni 30 Co 16 Al 11 alloy:

[0073] (1) According to the molecular formula Fe 43 Ni 30 Co 16 Al 11 Weigh 11.1143 g of 99.99% pure iron, 8.1485 g of nickel, 4.3636 g of cobalt, and 1.3734 g of aluminum, and place them in a non-consumable vacuum melting furnace for melting. The furnace vacuum reaches 3.0 × 10 -3 After Pa, argon gas is filled in for protection and the smelting is repeated for more than 4 times to obtain a metal ingot.

[0074] (2) Cut the ingot into the size of 2 mm × 6 mm × 13 mm.

[0075] Performance Testing

[0076] 1. Determination of superelasticity and strength of the alloys prepared in Examples 1 to 4:

[0077] Determination method: Cut the melted sample into a size of 4mm×4mm×8mm, and subject the sample to a compression test in a universal testing machine with a loading rate of 0.00025mm / s and an unloading rate of 0.5mm / min.

[0078] When testing the superelasticity and strength of the alloys prepared in Examples 1 to 4, the following results were obtained:

[0079] A. For the alloy prepared in Example 1, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm. The test results are as follows: Figure 1 As shown in the figure, it can be seen that when the strength is 1800MPa, the recoverable strain reaches 4%.

[0080] B. For the alloy prepared in Example 2, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm. The test results are as follows: Figure 2 As shown in the figure, it can be seen that when the strength is 2100MPa, the recoverable strain reaches 4.7%.

[0081] C. For the superelastic alloy prepared in Example 3, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm. The test results are as follows: Figure 3 As shown in the figure, it can be seen that when the strength is 3998MPa, the recoverable strain reaches 9.3%. 41 Ni 30 Co 16 Al 11 Cr1 has better compressive strength and higher recoverable strain.

[0082] D. For the alloy prepared in Example 4, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm, and the test results are as follows: Figure 4 As shown in the figure, when the strength is 4335MPa, the recoverable strain reaches 9.9%. Therefore, this heat treatment process also makes Fe 41 Ni 30 Co 16 Al 11 The compressive strength and superelasticity of Cr1 have been improved to a certain extent.

[0083] E. For the alloy prepared in Example 5, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm. The test results are as follows: Figure 5 As shown in the figure, when the strength is 4578MPa, the recoverable strain reaches 10.2%. Therefore, the heat treatment process also makes FFe 41 Ni 30 Co 16 Al 11 The compressive strength and superelasticity of Cr1 have been improved to a certain extent.

[0084] F. For the alloy prepared in Example 6, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm. The test results are as follows: Figure 6 As shown in the figure, when the strength is 4782MPa, the recoverable strain reaches 12.1%. Therefore, this heat treatment process also makes Fe 41 Ni 30 Co 16 Al 11 The compressive strength and superelasticity of Cr1 have been improved to a certain extent.

[0085] G. For the alloy prepared in Example 7, the sample size for testing its superelasticity and strength was 4mm×4mm×8mm. The test results are as follows: Figure 7As shown in the figure, it can be seen that when the strength is 4797MPa, the recoverable strain reaches 11.3%. Therefore, this heat treatment process also makes Fe 41 Ni 30 Co 16 Al 11 The compressive strength and superelasticity of Cr1 have been improved to a certain extent.

[0086] H. For the alloy prepared in Example 8, the sample size for testing its superelasticity and strength is 4mm×4mm×8mm. The test results are as follows: Figure 8 As shown in the figure, when the strength is 5108MPa, the recoverable strain reaches 12.5%. Therefore, this heat treatment process also makes Fe 41 Ni 30 Co 16 Al 11 The compressive strength and superelasticity of Cr1 have been greatly improved.

[0087] 2. Determination of the friction and wear properties of the alloys prepared in Example 1 and Comparative Examples 1-2:

[0088] I. For Fe prepared in Example 3 41 Ni 30 Co 16 Al 11 Fe prepared in Comparative Example 1 40 Ni 30 Co 16 Al 11 Cr2 and Fe prepared in Comparative Example 2 43 Ni 30 Co 16 Al 11 The friction coefficient test specimen size is 2mm×6mm×13mm. The test results are as follows: Fig. 9 As shown in the figure, it can be seen that with the introduction of Cr element, Fe 43 Ni 30 Co 16 Al 11 The friction coefficient of superelastic alloys is greatly reduced.

[0089] J. For Fe prepared in Example 3 41 Ni 30 Co 16 Al 11 Fe prepared in Comparative Example 1 40 Ni 30 Co 16 Al 11 Cr2 and Fe prepared in Comparative Example 2 43 Ni 30 Co 16Al 11 , test its wear amount, and the test results are as follows Fig.10 As shown in the figure, it can be seen that with the introduction of Cr element, Fe 43 Ni 30 Co 16 Al 11 The wear volume of superelastic alloys is drastically reduced.

[0090] According to Examples 1 to 8 and Comparative Examples 1 to 2, the compressive strength and superelasticity of the superelastic alloy are significantly improved by a reasonable heat treatment process, especially Fe 41 Ni 30 Co 16 Al 11 After 1000℃ solid solution treatment and 600℃ aging for 50h, the maximum compressive strength of Cr1 superelastic alloy increased from 3998MPa to 5108MPa, and the recoverable strain increased from 9.3% to 12.5%. 41 Ni 30 Co 16 Al 11 The compressive strength and corresponding recoverable strain of Cr1 superelastic alloy are shown in Table 1. 43 Ni 30 Co 16 Al 11 By adding Cr element to the material, its wear resistance is qualitatively improved, and its wear amount increases with the introduction of Cr element as shown in Table 2.

[0091] Table 1. Superelasticity and strength of each group of samples

[0092]

[0093] Table 2. Fe (40~43) Ni30Co16Al11Cr (0~2) Wear loss of superelastic alloy

[0094]

[0095] It can be seen from the above embodiments that the present invention provides a Fe-Ni-Co-Al-Cr superelastic alloy, the superelastic alloy has a strength of more than 5108MPa and a recoverable strain of 12.5%. The present invention provides a preparation method of the Fe-Ni-Co-Al-Cr alloy, and the superelastic alloy can be obtained by smelting, solid solution + aging treatment. The alloy has low production cost, simple preparation process, easy processing and molding, and is suitable for large-scale production.

[0096] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the techniques of the embodiments of the present invention.

Claims

1. A Fe-Ni-Co-Al-Cr superelastic alloy, characterized in that: The composition of the superelastic alloy is Fe a Ni b Co c Al d Cr e , where a, b, c, d, e represent the atomic percentage (at.%) of the corresponding element, a=35~50, b=20~35, c=10~20, d=5~18, e=0~3, and some inevitable impurities.

2. The Fe-Ni-Co-Al-Cr superelastic alloy according to claim 1, wherein the preparation method comprises the following steps: (1) Melting. Metal iron, nickel, cobalt, aluminum and chromium are weighed in proportion and arc-melted in a non-consumable vacuum arc furnace to obtain metal ingots for use; (2) Heat treatment: The heat treatment includes solution treatment and aging treatment.

3. The method for preparing a Fe-Ni-Co-Al-Cr superelastic alloy according to claim 2, characterized in that: The purity of the metals iron, nickel, cobalt, aluminum and chromium is equal to or greater than 99.9%.

4. The method for preparing a Fe-Ni-Co-Al-Cr superelastic alloy according to claim 2, characterized in that: The vacuum degree of arc melting in step (1) is less than 3×10 -3 Pa, and the smelting process is carried out under argon protection.

5. The method for preparing a Fe-Ni-Co-Al-Cr superelastic alloy according to claim 2, characterized in that: The metal ingot subjected to arc melting in step (1) is repeatedly melted more than three times to ensure uniform alloy composition.

6. The method for preparing a Fe-Ni-Co-Al-Cr superelastic alloy according to claim 2, characterized in that: The heat treatment process in step (2) is: solution treatment at 1000-1300° C. for 1-8 hours, and then aging at 500-800° C. for 5-120 hours.